Public Participation in the Local Development Plan, B.E.2566-2570 of Samed Subdistrict Municipality, Mueang Chon Buri District, Chon Buri Province: Public Participation in the Local Development Plan, B.E.2566-2570 of Samed Subdistrict Municipality, Mueang Chon Buri District, Chon Buri Province - Manohong, Chonlada; Sueprasertsith, Chakchai (RATANABUTH JOURNAL, 2026)
The Objectives of research were (1) To study the level of public participation in the local development plan B.E. 2566-2570 (2023 - 2027) of Samed subdistrict municipality, Mueang Chon buri district, Chon buri province and (2) To study the factors affecting public participation in the local development plan B.E. 2566-2570 (2023 - 2027) of Samed subdistrict municipality, Mueang Chon buri district, Chon buri province. The informants in this research consisted of a sample group of 213 citizens aged 18 years and over residing in the Samet Subdistrict Municipality area, Mueang Chonburi District, Chonburi Province, whose sample size was determined using the G*Power program and selected through multi-stage random sampling, and 43 individuals from the subdistrict-level local community, accounting for 86 percent of the total population. The research instrument for collecting data was a questionnaire. Data were analyzed using descriptive statistics, including percentage, mean, and standard deviation, and inferential statistics, namely Multiple Linear Regression with Dummy Variables. The results show that 1) the level of public participation in the local development plan B.E. 2566-2570 (2023 - 2027) of Samed subdistrict municipality, Mueang Chon buri district, Chon buri province is at a high level. When considered on each aspect of public participation, it was found that the participatory actions of local development plans B.E. 2566-2570 (2023 - 2027) Samet Sub-district Municipality, Mueang Chonburi District, Chonburi Province in the highest mean score, the second is the aspect of receive benefits, the third is the aspect of monitoring and inspection, the fourth is the aspect of consultation, the fifth is the aspect of providing information to the public, the sixth is the aspect of general and basic local information awareness, the seventh is the aspect of decision making and the last is the aspect of participatory planning 2) The factors that result in the participation in the local development plan B.E. 2566-2570 (2023 - 2027) of Samed subdistrict municipality, Mueang Chon buri district, Chon buri province include previous experience, primary stakeholders, local executive policies, characteristics of society, social or community values and complaints about problems in the community were statistically significant at .01